2023
DOI: 10.3390/en16010541
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Upgrading of Plastic Waste of Electric and Electronic Equipment (WEEE) Pyrolysis Vapors over Si–Al Ash Pellets in a Two-Stage Reactor

Abstract: This study investigated thermal cracking and catalytic upgrading of waste from electric and electronic equipment (WEEE) plastics on a semi-batch reactor coupled to a heated catalyst fixed bed (2-stage vapor cracking). The catalyst used is a Si–Al ash obtained from commercial activated carbon pellets treated with concentrated NaOH solution and calcination. The purpose of the study was to characterize the waste stream through its thermogravimetry analysis and pyrolysis products, study the effect of temperature (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 83 publications
1
4
0
Order By: Relevance
“…Unlike on the technical and pilot scales, the reactor temperature thermocouple was situated outside of the reactor, and actual reactor temperatures were possibly lower, while for the technical and pilot scales, the thermocouple is situated in the center of the fixed bed, and temperatures at the edges of the reactors are higher than the setpoint of 450 • C, augmenting the production of side products in liquid and gaseous phases. The slower heating rates in the larger fixed bed of PMMAW also increased char yields with process scale, corroborating what is observed in academic literature for many types of materials [55][56][57]. Since pyrolysis process products are influenced by temperature and heating rates, it can be concluded that the characteristics of the feed such as specific heat, thermal conductivity and particle size and the characteristics of the process such as reactor geometry, heating mode and residence time are connected to temperature effects, influencing the yields of products.…”
Section: Scaling-up Effect On the Yield Of Productssupporting
confidence: 88%
See 2 more Smart Citations
“…Unlike on the technical and pilot scales, the reactor temperature thermocouple was situated outside of the reactor, and actual reactor temperatures were possibly lower, while for the technical and pilot scales, the thermocouple is situated in the center of the fixed bed, and temperatures at the edges of the reactors are higher than the setpoint of 450 • C, augmenting the production of side products in liquid and gaseous phases. The slower heating rates in the larger fixed bed of PMMAW also increased char yields with process scale, corroborating what is observed in academic literature for many types of materials [55][56][57]. Since pyrolysis process products are influenced by temperature and heating rates, it can be concluded that the characteristics of the feed such as specific heat, thermal conductivity and particle size and the characteristics of the process such as reactor geometry, heating mode and residence time are connected to temperature effects, influencing the yields of products.…”
Section: Scaling-up Effect On the Yield Of Productssupporting
confidence: 88%
“…All three fixed bed pyrolysis plants were accurately described in previous works [9,[55][56][57][58][59][60][61][62][63]. Basically, the three reaction systems are constructed based on a classic semibatch pyrolysis system (Figure 2) composed of a heated temperature-controlled fixed bed reactor coupled with a tube condenser operating with cooling water.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An overall mass balance was performed in order to calculate the quantity of gas formed. Basically, the weights of feed, bio-oil, aqueous phase, and coke formed are recorded, and a global integral mass balance calculation yields the quantity of gas formed by difference [85,86]. A differential mass balance of the considered system is described by Equation (1):…”
Section: Mass Balances By Pyrolysis Of Açaí Seedsmentioning
confidence: 99%
“…An overall mass balance was done in order to calculate the quantity of gas formed. Basically, the weight of feed, bio-oil, aqueous phase and coke formed are recorded and a global integral mass balance calculation yields the quantity of gas formed by difference [54][55]. A differential mass balance of the considered system is described by the following equation ( 1):…”
Section: Mass Balances By Pyrolysis Of Açaí Seedsmentioning
confidence: 99%